Risk level of factors causing construction waste generation throughout construction project life cycle - Md Akhir, Nor Solehah (2015)
The construction industry has an adverse impact on the environment from the wastes generated during construction work. The amount of wastes generated increases yearly due to rapid economic growth worldwide which includes Malaysia. Due to waste generation, one of the major issues faced is the increase of illegal dumpsites. The illegal dumping may caused a risk to human health and environment. Thus, it calls for serious measures to regulate wastes generation. The waste is generated due to various factors throughout construction project life cycle (CPLC). For controlling purpose, it is very important to identify the generation factors and also to determine the level of risk from each factor. Hence, this study focuses on assessing the risk level of factors causing wastes generation throughout CPLC. Besides, it also proposes mitigation measures for the high risk factors. For assessing the risk level, a total of 33 factors that causes construction wastes generation that have been identified from literature review were considered. The assessment involved 15 experts who are experienced in handling construction projects. This investigation adopted two rounds of Delphi method in determining level of occurrence and severity of each factor in relation with different phases of CPLC. The experts were required to fill out the questionnaire set and the analysis on the gathered data from the questionnaire work was done using risk matrix. The result indicated that in the construction phase, majority of the identified factors occurred in this phase are critical due to having high risk level and most of them are categorised in Human Resource/Manpower (HRM) group. It is followed by finishing phase, design phase, and planning phase. However, in planning phase, the chances of wastes generation are minimal with no high risk factors. In order to control the construction wastes generation problem, mitigation measures for high risk factors were proposed. The findings of this study can be a useful guide for the practitioners in controlling construction wastes generation.